EFFECT OF LISINOPRIL ON MICROALBUMINURIA - Qureshi, Khalid Mahmood; Ahmed, Raja Zafar; Taseer, Ijazul Haq; Khan, Misbahul Islam; Pasha, Nusrat (Journal of Ayub Medical College Abbottabad, 1999)
The purpose of this study was to evaluate the effect of Lisinopril on microalbuminuria in non- insulin dependent diabetic hypertensive patients. One hundred and twenty patients were divided into two groups. Croup-A was given placebo of Lisinopril and Group-B was given Lisinopril in a fixed dose of 10 mg once daily for two weeks. Comparison of microalbuminuria before and after the treatment showed a decrease in microalbuminuria level in patients treated with Lisinopril.